HIGH DEFINITION ECG: FROM PRESENT TO FUTURE - I. A. Latfullin; Z. F. Kim; G. M. Teptin; L. E. Mamedova (Российский кардиологический журнал)
The study was aimed at assessing qualitative characteristics of late ventricular potentials (LVP) in 104 patients with various clinical forms of coronary heart disease (CHD). LVP assessment was performed at Days 3, 7, and 14 after admission to the acute cardiac care unit. The control group included 49 relatively healthy volunteers. For the majority of LVP and LVP spectre records, the amplitudes were consistent with the Gaussian random distribution. In addition, short and long-term dynamics of LVP parameters was investigated, after calculation of wavelet spectre and complex spectre module for each signal. To identify the high-correlation frequencies for paired leads, the cross-wavelet LVP analysis was used.